A Study on a New 3D Porous Polymer Printing Based on EPP Beads Containing CO2 Gas. (2017) - Yoo, C.J.; Shin, B.S.; Kang, B.S.; Gwak, C.Y.; Park, C.; Ma, Y.W.; Hong, S.M.
Abstract: We propose a new CO2 gas-based 3D PPP (Porous Polymer Printing) developed based on the Fused Deposition Modeling scheme of Additive Manufacturing. The 3D porous polymer structure was stacked layer by layer, which was a rapid single step manufacturing technique for a multilayer product in single device. A hybrid filament of diameter 1.75 mm was introduced with EPP (Expanded Polypropylene) beads containing CO2 gas. EPP beads, which have several desirable characteristics such as light weight, shock absorption, thermal insulation, heat resistance, weather resistance, oil resistance, and chemical resistance, were also subject to various process conditions such as EPP type, laminate thickness, printing speed and nozzle temperature. In this paper, three types of EPP beads with expansion ratios of 15, 30 and 40% were investigated. We found the experimentally optimal process conditions of a new CO2 gas-based 3D PPP method and finally demonstrated a simple 3D structure. In the future, a faster production and the mechanical shock absorption effect will be studied and tested for application in the automobile industry.